2008
DOI: 10.1007/s00018-008-8321-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A: An acute-phase protein involved in tumour pathogenesis

Abstract: The synthesis of acute-phase protein serum amyloid A (SAA) is largely regulated by inflammation- associated cytokines and a high concentration of circulating SAA may represent an ideal marker for acute and chronic inflammatory diseases. However, SAA is also synthesized in extrahepatic tissues, e.g. human carcinoma metastases and cancer cell lines. An increasing body of in vitro data supports the concept of involvement of SAA in carcinogenesis and neoplastic diseases. Accumulating evidence suggests that SAA mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
181
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(199 citation statements)
references
References 202 publications
5
181
0
6
Order By: Relevance
“…Proposed candidate receptors for SAA1 and SAA2 include the receptor for advanced glycation endproducts and TLR2. 4 Metastasis has been studied from the standpoint of intrinsic tumor cell properties and host responses, including angiogenesis and immune surveillance at primary sites. On the one hand, given that adaptive antitumor immunity of endogenous origin, in general, fails to work efficiently in clinical settings, much effort has been made to abrogate immunoediting in tumor cells by modifying naturally occurring tumor antigens and manipulating dendritic cells (DCs), which bridge innate and adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Proposed candidate receptors for SAA1 and SAA2 include the receptor for advanced glycation endproducts and TLR2. 4 Metastasis has been studied from the standpoint of intrinsic tumor cell properties and host responses, including angiogenesis and immune surveillance at primary sites. On the one hand, given that adaptive antitumor immunity of endogenous origin, in general, fails to work efficiently in clinical settings, much effort has been made to abrogate immunoediting in tumor cells by modifying naturally occurring tumor antigens and manipulating dendritic cells (DCs), which bridge innate and adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
“…SAA has been documented as acute-phase reactant whose level in the blood is elevated to 1000-fold as part of the body's responses to various injuries, including trauma, infection, inflammation, and neoplasia. Functions of SAA describing to tumourigenesis (Malle et al, 2009) by attaching to extracellular matrix components with consequent potential modification of cell binding, augmentation of plasminogen activation and triggering of matrix metalloproteinase (MMP) production, and was accounted in numerous cell forms including renal cancer cell lines (Paret et al, 2010). Another inflammatory acute phase protein is CRP.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, although the biological importance of SAA in USPC patients is not well understood, previous reports have suggested multiple important biologic functions of SAA. Indeed, SAA has been previously reported to be involved in cholesterol metabolism and transport, inhibition of lymphocyte, and endothelial cell proliferation, depression of the immune system, inhibition of platelet aggregation, and induction of adhesion, migration, and tissue infiltration of monocytes, neutrophils, lymphocytes, and mast cells (Malle et al, 2009).…”
Section: Healthymentioning
confidence: 99%
“…Using this technology, our group has recently evaluated the genetic fingerprints of USPC (Santin et al, 2004. Among the several candidate target genes identified, the gene encoding for human serum Amyloid A (SAA), an HDL-associated lipoprotein known to have a major role as a modulator of inflammation and in the metabolism and transport of cholesterol (Yamada, 1999;Malle et al, 2009), was consistently found as one of the top upregulated genes in USPC. In humans the SAA gene family consists of three genes (SAA1, SAA2, and SAA4) and a (pseudo) gene (SAA3) (Malle et al, 2009), all clustered on the short arm of chromosome 11.…”
mentioning
confidence: 99%
See 1 more Smart Citation